The goldrim surgeonfish (Acanthurus nigricans; Acanthuridae) from Diego Garcia, Chagos Archipelago: first record for the central Indian Ocean - Craig, Matthew T. (Zootaxa, 2008)
The goldrim surgeonfish (also known as the whitecheek surgeonfish in the aquarium trade), Acanthurus nigricans (Linnaeus), is a common and widespread member of tropical reef fish communities throughout the Pacific Ocean. It has been reported at low densities at Cocos (Keeling) and Christmas Islands in the eastern Indian Ocean. Named nigricans for its characteristically dark body color, the species usually inhabits shallow depths on the outer reef crest just below the surge zone, but has been observed as deep as 67 m (Chave and Mundy, 1994). The species feeds on filamentous algae (Randall, 2001). In this paper I report the first occurrence of Acanthurus nigricans in the central Indian Ocean (Chagos Archipelago) and provide information on its biogeography and hybridization with A. leucosternon Bennett.